Upgrading the State‐of‐the‐Art Electrocatalysts for Proton Exchange Membrane Fuel Cell Applications. Issue 17 (4th May 2022) - Fang, Baizeng; Daniel, Lius; Bonakdarpour, Arman; Wilkinson, David P.
Abstract: Carbon‐supported Pt‐based electrocatalysts have been widely investigated for diverse electrochemical energy storage and conversion applications. Vulcan XC72R (VC) supported Pt(20 wt%) nanoparticles (NPs) (denoted as Pt(20 wt%)NPs/VC produced by Johnson Matthey (JM)) is the most commonly‐used catalyst and is thus widely considered to be the state‐of‐the‐art electrocatalyst. Although Pt(20 wt%)NPs/VC(JM) has demonstrated very good electrocatalytic performance in these applications, further improvement in its electrocatalytic activity and electrochemical stability is still highly desired. In this study, an innovative strategy, involving graphitic carbon nitride (g‐CN) coating of the electrocatalyst, is shown to improve the performance. Although other researchers have attempted modifying the support and components during the process of making an electrocatalyst, the authors report, for the first time, the nitriding of an existing catalyst, that is, post‐modification of the electrocatalyst. Due to the unique features of g‐CN coating, which include high chemical stability, good oxygen adsorption and improved ionomer distribution in the catalyst layer, the g‐CN‐coated Pt(20wt%)NPs/VC(JM) electrocatalyst (g‐CN content: 0.61 wt%) has demonstrated both improved polarization performance and electrochemical stability. This simple but very effective strategy is believed to open a new avenue for improvement of electrocatalytic performance for a range of diverse commercially‐available electrocatalysts used in proton exchange membrane fuel cells. Abstract : Improvement in electrochemical stability of Pt‐based cathode electrocatalysts is among the highest priorities in the development of hydrogen‐fed proton exchange membrane fuel cells. Here the authors demonstrate an innovative engineering strategy through which electrocatalyst is coated with a thin protective graphitic carbon nitride layer resulting in improved performance.